A pedagogia é feminizada? Gênero e identidade profissional de graduandos/as e egressos/as - Freitas, Mayanne Julia Tomaz (2024)
In Brazil, Pedagogy (Teacher Education) has consolidated itself as a feminilized field, that is, with a massive presence of women from training to professional activity; consequently, its probable feminization stands out, in terms of meanings and values associated with professional identity. This study aims to analyze how gender marks are present in social representations about Pedagogy and in the professional identity of undergraduates and graduates of the program at Federal University of Paraíba (UFPB), campus I. Guiding questions are: Considering that gender relations structure knowledge and work, what does the gendering/feminization of Pedagogy mean? Does the feminilization/the high number of women in Pedagogy translate into feminization? Specific questions can be explored based on the sociodemographic profile of students and graduates of the aforementioned program: What social representations about Pedagogy and its professionals do undergraduates and graduates have? Do these social representations contain gender marks? Did they influence their choice to study and work in Pedagogy? Do they point to possibilities for changing professional identities? The research, inspired by the Theory of Social Representations (TRS), uses mixed methods, through three movements of production and analysis of quantitative and qualitative data. The first involves documentary analysis of the evolution of the program's curricular proposals and quantitative data on student entry and completion, from 2006 to 2021. In 2006 the new National Curricular Guidelines for Pedagogy (DCNPs) was approved, as well as the pedagogical project for the UFPB program, still in force. The second consists of the analysis of 180 questionnaires applied to undergraduate students, from May to October 2020 and from April to June 2021, in the context of the research project “Social representations of professional and gender identities by Pedagogy and Engineering students: a comparative study at UFPB and UFU”, financed by CNPq. The third reached 157 graduates from classes from 2006 to 2022, through the application of an online questionnaire from February to July 2023. The analysis of results highlights the identity of the Pedagogy program in Brazil based on its historical milestones, the DCNPs, the debate about its epistemological status and the kinds of activities performed of the pedagogue, as well as the experiences, perceptions and professional perspectives of 180 undergraduates and 157 graduates of the UFPB program, informed in the questionnaires; it also highlights the performance of the program, based on data on entry, dropout, retention and completion, and the professional apportionments of graduates. In conclusion, data from undergraduates and graduates on training, performance and social representations of Pedagogy and its professional are articulated. Thus, the thesis confirms that the training and performance of the pedagogue still present gender marks, in such a way that men who choose the program see Pedagogy as a scientific field more than women, who are trapped in the association of Pedagogy with love and care. Furthermore, the thesis also indicates that past and present professional training is unable to change the gendering of Pedagogy due to the historical association between women and teaching and the incipient problematization of gender issues in the curriculum.